Pollution Abatement in the Netherlands: A Dynamic Applied General Equilibrium Assessment - Rob Dellink; Ekko van Ierland (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper deals with an assessment of the economic costs of environmental policies in the Netherlands, using a dynamic Applied General Equilibrium model with bottom-up information on abatement techniques. Empirical abatement cost curves are used to determine substitution possibilities between pollution and abatement and the characteristics of abatement goods. The results show that an absolute decoupling of economy and environment is possible. Smog formation is the most costly environmental theme, due to the absence of technical abatement options. For all environmental themes, the least-cost way to reduce emissions is via a combination of technical abatement measures and substantial economic restructuring.
Keywords: D58; H23; O41; Q28; 330; Applied general equilibrium; Pollution abatement; Dynamics; Environmental policy; Netherlands; Umweltkosten; Allgemeines Gleichgewicht; Umweltpolitik; Niederlande